Barriers to rehabilitation after critical illness: a survey of multidisciplinary healthcare professionals caring for ICU survivors in an acute care hospital. Issue 3 (May 2020) - Rai, Sumeet; Anthony, Lakmali; Needham, Dale M.; Georgousopoulou, Ekavi N.; Sudheer, Bindu; Brown, Rhonda; Mitchell, Imogen; van Haren, Frank
Abstract: Background: There is scant literature on the barriers to rehabilitation for patients discharged from the intensive care unit (ICU) to acute care wards. Objectives: The objective of this study was to assess ward-based rehabilitation practices and barriers and assess knowledge and perceptions of ward clinicians regarding health concerns of ICU survivors. Methods, design, setting, and participants: This was a single-centre survey of multidisciplinary healthcare professionals caring for ICU survivors in an Australian tertiary teaching hospital. Main outcome measures: The main outcome measures were knowledge of post–intensive care syndrome (PICS) amongst ward clinicians, perceptions of ongoing health concerns with current rehabilitation practices, and barriers to inpatient rehabilitation for ICU survivors. Results: The overall survey response rate was 35% (198/573 potential staff). Most respondents (66%, 126/190) were unfamiliar with the term PICS. A majority of the respondents perceived new-onset physical weakness, sleep disturbances, and delirium as common health concerns amongst ICU survivors on acute care wards. There were multifaceted barriers to patient mobilisation, with inadequate multidisciplinary staffing, lack of medical order for mobilisation, and inadequate physical space near the bed as common institutional barriers and patient frailty and cardiovascular instability as the commonly perceived patient-related barriers. A majority of the surveyed ward clinicians (66%, 115/173) would value education on health concerns of ICU survivors to provide better patient care. Conclusion: There are multiple potentially modifiable barriers to the ongoing rehabilitation of ICU survivors in an acute care hospital. Addressing these barriers may have benefits for the ongoing care of ICU survivors.